Digital Communication and Representational Interactivity: an Analysis of www.WriteToThem.com in Scotland. Issue 1 (10th June 2017) - Pautz, Hartwig
Abstract: The potential of the Internet to address deficits in the relationship between representatives and represented has been discussed for some time. This article analyses whether 'www.WriteToThem.com ', an online tool allowing people to contact their elected members of local, subnational, national and European parliaments, promotes 'interactivity' between elected and electors. The analysis uses data from a survey and interviews with Scottish local councillors and Members of the Scottish Parliament. The article finds that WriteToThem.com is not suitable to generate high levels of interactivity between citizens and the elected and is used for purposes not intended by its makers nor necessarily appreciated by the elected.